PENGUATAN STRATEGI PENANGKALAN DALAM MERESPONS AKSI KOERSIF CINA DI LAUT NATUNA UTARA - Boy Anugerah (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2021)
Abstract China’s claims to all areas in the South China Sea have caused conflict with several states, such as Malaysia, the Philippines, Vietnam, Brunei Darussalam, and Taiwan. China’s claims are based on historical aspects by referring to the nine-dash line map, whether other claimant states are based on the UNCLOS 1982. Indonesia initially acted as a non-claimant state in this conflict. However, along with many violations committed by China in the North Natuna Sea, which is the Indonesian Exclusive Economic Zone, Indonesia is increasing its national vigilance. China is playing smart by pursuing a grey zone strategy. China’s strategy requires Indonesia to strengthen its deterrence strategy. This research uses a qualitative approach. Desk research is conducted as the collection data method. The results of this study indicate that it is necessary to strengthen Indonesia’s deterrence strategy, both military and non-military approaches. Keywords: coercion, deterrence, North Natuna Sea, South China Sea, Strategy